2016
DOI: 10.1007/s10653-016-9854-9
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition of Malawian rice

Abstract: Widespread potential dietary deficiencies of calcium (Ca), iron (Fe), iodine (I), selenium (Se) and zinc (Zn) have been identified in Malawi. Several deficiencies are likely to be compounded by high phytic acid (PA) consumption. Rice (Oryza sativa) is commonly consumed in some Malawian populations and its mineral micronutrient content is important for food security. The considerable irrigation requirements and flooded conditions of paddy soils can also introduce or mobilise potentially toxic elements including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
3
19
1
1
Order By: Relevance
“…Similar trends were observed by Seyfferth, Webb, Andrews, & Fendorf (2011) and Rahman & Hasegawa (2011). Mean iAs value determined in UPR using FDM (mean: 52±18 µg/kg compared well to mean iAs of 60 µg/kg reported by Joy et al (2016) for unpolished (brown) Malawian rice. The mean iAs concentration in polished Malawian rice (mean: 31±12 µg/kg; range 9 -54 µg/kg) is amongst the lowest ever reported concentrations for iAs in rice worldwide (Meharg et al, 2009;P.…”
Section: Variation Of Ias Values Determined By On-site Fdmsupporting
confidence: 81%
“…Similar trends were observed by Seyfferth, Webb, Andrews, & Fendorf (2011) and Rahman & Hasegawa (2011). Mean iAs value determined in UPR using FDM (mean: 52±18 µg/kg compared well to mean iAs of 60 µg/kg reported by Joy et al (2016) for unpolished (brown) Malawian rice. The mean iAs concentration in polished Malawian rice (mean: 31±12 µg/kg; range 9 -54 µg/kg) is amongst the lowest ever reported concentrations for iAs in rice worldwide (Meharg et al, 2009;P.…”
Section: Variation Of Ias Values Determined By On-site Fdmsupporting
confidence: 81%
“…Another study from China found results similar to ours [78]. Rice is the main staple of Asians, but in current high-yielding rice varieties the supply of zinc is poor, as polishing and shelling cause a huge loss of zinc [81,82]. Other reason is possible that discrepancies in levels of trace elements between different countries are partly due to environmental factors, but specific reasons need to be explored further.…”
Section: Discussionsupporting
confidence: 67%
“…There has been limited survey of arsenic in African rice (Adeyemi et al 2017;Adomako et al 2011;Joy et al 2017). The finding that East African rice is low in arsenic confirms a study which reported that Malawian paddy rice was particularly low in total arsenic (Joy et al 2017). The underlying geology of the East African region surveyed, stretching from southern Malawi to northern Tanzania, has a diverse topology and geology (McConnell 1972), yet is universally low in inorganic arsenic.…”
Section: Discussionmentioning
confidence: 61%
“…There has been limited survey of arsenic in African rice (Adeyemi et al 2017;Adomako et al 2011;Joy et al 2017). The finding that East African rice is low in arsenic confirms a study which reported that Malawian paddy rice was particularly low in total arsenic (Joy et al 2017).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation